MARKETING COMMUNICATION CAPACITY OF GAYO COFFEE MSMES ACTORS IN CENTRAL ACEH REGENCY - Harahap, Rahmat Dilta; Amanah, Siti; Wibowo, Cahyono Tri (Sosiohumaniora, 2025)
This study aims to (1) describe the marketing communication practices of Gayo Coffee MSME actors and (2) analyze the influence of internal factors, external factors, and communication behavior on the marketing communication capacity of Gayo Coffee MSME actors. This research is a quantitative study with a non-experimental research design. A total of 88 respondents who are Gayo Coffee MSME actors in Central Aceh Regency with small business scale (68.2%) and micro business scale (31.8%) were used as samples. The data analysis technique used was descriptive analysis and SEM-PLS analysis using SmartPLS 3.0 software. The results showed that marketing communication practices applied to Gayo Coffee MSMEs include advertising, sales promotion, direct marketing, and interactive marketing activities.  Internal factors of Gayo Coffee MSME actors consisting of age, formal education level, participation in training, and motivation have a significant effect on marketing communication capacity, the motivation indicator is the most influential internal factor. External factors of Gayo Coffee MSME actors consisting of capital, length of business, and number of workers affect the marketing communication capacity of the business length indicator is the most influential external factor. The communication behavior of Gayo Coffee MSME actors, which includes cosmopolitanism, activeness in seeking information, accessibility and media utilization, also affects marketing communication capacity. Activeness in seeking information is the most influential indicator of communication behavior, indicating that MSME actors who are open to new information and actively use digital communication media tend to be more successful in implementing effective marketing communications.